EFEKTIVITAS PENANGANAN DAN PERLINDUNGAN ORANG DENGAN GANGGUAN JIWA OLEH DINAS KESEHATAN KABUPATEN MANGGARAI BERDASARKAN UNDANG-UNDANG NOMOR 18 TAHUN 2014 TENTANG KESEHATAN JIWA - Afra, Paulinus; Yohanes, Saryono; Monteiro, Yosef Mario (Petitum Law Journal, 2025)
The escalating global prevalence of mental health disorders underscores the critical need for effective governmental interventions. This study delves into the efficacy of mental disorder management within Manggarai Regency, Indonesia, guided by the framework of Law No. 18 of 2014 concerning Mental Health. Utilizing an empirical juridical research approach, data was meticulously gathered through a combination of interviews, direct observations, and thorough document analysis. The findings reveal a concerning reality: the Manggarai Regency Health Office's current strategies for addressing mental disorders have proven to be largely ineffective, as evidenced by a substantial surge in reported cases. Key impediments to successful management include deficiencies in essential facilities and infrastructure, compounded by the challenge of inconsistent and insufficient funding. To rectify these shortcomings, the study strongly advocates for the Health Office to intensify its efforts across the spectrum of mental health services, encompassing promotive, preventive, curative, and rehabilitative initiatives. Furthermore, the regional government is urgently called upon to bolster its support for the Health Office, ensuring that it is adequately equipped to tackle the complex challenges posed by mental health disorders.